2011
DOI: 10.1007/s12640-011-9257-8
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Pre-conditioning Reduces Brain Inflammation and Protects against Toxicity Induced by Traumatic Brain Injury: Behavioral and Neurochemical Approach

Abstract: Although the favorable effects of physical exercise in neurorehabilitation after traumatic brain injury (TBI) are well known, detailed pathologic and functional alterations exerted by previous physical exercise on post-traumatic cerebral inflammation have been limited. In the present study, it is showed that fluid percussion brain injury (FPI) induced motor function impairment, followed by increased plasma fluorescein extravasation and cerebral inflammation characterized by interleukin-1β, tumor necrosis facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 61 publications
6
28
0
Order By: Relevance
“…Our results demonstrated that group membership determined changes between interventions and controls in this parameter, while there was also a trend for baseline CCI and change in IL-1β to be independently associated with change in S100β. Despite not inferential, this result suggests the possibility that fluctuations in BBB integrity may be related to modulation of inflammatory cytokines, which is consistent to those investigations in animal model mentioned above (Mota et al 2012, Souza et al 2016). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results demonstrated that group membership determined changes between interventions and controls in this parameter, while there was also a trend for baseline CCI and change in IL-1β to be independently associated with change in S100β. Despite not inferential, this result suggests the possibility that fluctuations in BBB integrity may be related to modulation of inflammatory cytokines, which is consistent to those investigations in animal model mentioned above (Mota et al 2012, Souza et al 2016). …”
Section: Discussionsupporting
confidence: 92%
“…Production of TNF-α directly affects the BBB permeability (Larochelle et al 2011). Evidence has shown that physical exercise inhibited the production of pro-inflammatory cytokines, upregulated the regulatory T cells, and suppressed IL-6 and TNF-α production associated with the inhibition of adhesion molecules and reestablishment of tight junction protein expression, thereby restraining BBB permeability (Mota et al 2012, Souza et al 2016. Our exercise results clearly showed a decrease in the IL-1β/IL-1ra, IL-6/IL10 and TNF-α/IL-10 ratios.…”
Section: Discussionmentioning
confidence: 99%
“…EX-TBI mice displayed significant reductions in sensorimotor deficits when compared to NOEX-TBI mice at all three post-TBI time points. This finding supports research by Mota et al, who revealed 4 weeks of pre-TBI treadmill training reduced post-TBI motor deficits in rats, and decreased blood-brain barrier breakdown and neuroinflammation (Mota et al, 2012). …”
Section: Discussionsupporting
confidence: 91%
“…Infarct size following forebrain ischemia was shown to present altered inflammatory status by profile performing exercise before brain trauma with prophylactic effects on brain damage (Endres et al 2003; see also Ding et al 2006). Pre-TBI physical training was found to induce interleukin-10 increase per se and protected against cerebral interleukin-1b and tumor necrosis factor-a increases and fluid perfusion induced brain damage decrements in interleukin-10 ( Mota et al 2011).…”
Section: Anti-inflammatory and Angiogenic Effects Of Exercise: Tbimentioning
confidence: 99%
“…In this regard, Nation et al (2011) have presented a neurovascular pathway of neurodegenerative disorder that underlines exercise as an intervention against vascular risk factors that include hypertension, diabetes, and aortic rigidity as well as direct changes in cerebrovasculature that involve changes in cerebral blood flow, angiogenesis and vascular disease improvement. Mota et al (2011) have shown that exercise preconditioning reduced cerebral inflammation and protected against TBI-induced toxicity; cardiovascular adaptation to physical exercise (Scheuer and Tipton 1977) offers a necessary adjunct to cerebrovascular integrity. Aerobic exercise reduces mortality in cardiovascular disorder (Taylor et al 2004), benefits mood (Blumenthal et al 1999), decreased impulsiveness in ADHD children (Medina et al 2010), diminishes anxiety and depression (Lewin et al 1992), and improves cognition (Colcombe and Kramer 2003;Gunstad et al 2005).…”
Section: Anti-inflammatory and Angiogenic Effects Of Exercise: Tbimentioning
confidence: 99%